Relationship Between of Lactate Clearance with Major Cardiovascular Events in Patients with Acute Decompensated Heart Failure - David Ramli; Masrul Syafri; Muhammad Fadil; Ricvan Nandra Nindrea (Jurnal Kardiologi Indonesia, 2018)
ABSTRACT Background: Acute decompensated heart failure (ADHF) still a major health problem with high morbidity and mortality. The risk stratification of ADHF patients is an important factor to determine the initial management. Examination of lactic acid levels is an inexpensive tool and mostly available at primary care centers. Lactate clearance, derivation of lactic acid level, is one of the modalities that can be used to assess risk stratification. The association between lactate clearance and in-hospital major cardiovascular events (MACE) of ADHF patients has not been studied yet. Method: Observational approach with cross-sectional design. Data obtained from observations during treatment in ADHF patients at Dr. RSUP M. Djamil Padang in April-July 2018. Bivariate analysis between variables lactate clearance and KKM was carried out during the treatment using the chi-square method and the Odds ratio was obtained. Result: From 44 subjects, 22 of subjects experienced MACE. From the results were found significant differences in lactate clearance in both of groups, -11,72 ± 4,25 %, vs 26,09 ± 9,36 % (p=0,000). The association between lactate clearance and in-hospital major cardiovascular events of ADHF patients in this study obtained OR 1,16 with 95% CI 1,12 - 4,102 (p = 0.000). Conclusion: Lactate clearance is a valuable modality that can be used to make a risk stratification in ADHF patients. Keywords: Lactate clearance, ADHF, risk stratification ABSTRAK Latar Belakang: Gagal jantung dekompensata akut (ADHF) masih merupakan masalah kesehatan dengan morbiditas dan mortalitas tinggi. Stratifikasi risiko pasien ADHF merupakan faktor penting untuk menentukan managemen awal. Pemeriksaan kadar asam laktat merupakan alat yang murah dan tersedia di pusat pelayanan primer, lactate clearance merupakan salah satu modalitas untuk menilai stratifikasi risiko. Hubungan antara lactate clearance dengan kejadian kardioavaskular mayor selama perawatan pada pasien ADHF belum diteliti. Metode Penelitian: Pendekatan observasional dengan desain potong lintang. Data diperoleh dari pengamatan selama perawatan pada pasien ADHF di RSUP Dr. M. Djamil Padang bulan April-Juli 2018. Dilakukan analisis bivariat antara varibel lactate clearance dengan KKM selama perawatan dengan menggunakan metode chi-square dan didapatkan nilai Odds ratio. Hasil Penelitian : Dari 44 subyek penelitian, 22 subjek dengan ADHF tidak mengalami KKM dan 22 subjek mengalami KKM. Hasil penelitian menemukan adanya perbedaan yang bermakna variabel lactate clerance pada kedua kelompok, yakni -11,72 ± 4,25 % vs 26,09 ± 9,36 %, dengan nilai p=0,000. Hubungan antara lactate clearance dengan kejadian kardioavaskular mayor selama perawatan pada pasien ADHF pada penelitian ini didapatkan nilai OR 1,16 dengan 95% CI 1,12 - 4,102 (nilai p=0,000). Kesimpulan : Lactate clearance dapat digunakan sebagai stratifikasi risiko pada pasien ADHF. Kata kunci : Lactate clearance, ADHF, stratifikasi risiko